The Role of Blockchain Technology in the Evolution of Journalism (Mongolian Journal of Humanities and Social Sciences, 2025)
Blockchain technology has significantly influenced the development of journalism. Media outlets based on blockchain technology operate with decentralized databases, free from control and censorship, ensuring press freedom and contributing to the advancement of independent journalism. In this research paper, we examine the fundamental role of blockchain technology in journalism development through five key aspects:  • Combating Fake News: Since blockchain records information immutably, it plays a crucial role in fighting misinformation.• Decentralized Platforms: With the emergence of decentralized platforms, authorities or any other entities cannot delete or manipulate information.• Financial Independence: Various cryptocurrencies based on blockchain support the financial independence of media organizations by allowing direct donations to editors and journalists.• Intellectual Property Protection: Journalistic content can be converted into NFTs using blockchain technology, providing a direct solution to intellectual property issues.• Transparency and Source Verification: Blockchain-based media ensure transparency in journalism, helping to verify the authenticity and origin of news.However, the full adoption of blockchain technology faces challenges such as financial resources, users' technological capabilities, legal regulations, and technical advancements. If these challenges are addressed, blockchain-based media could fully determine the future direction of journalism.Блокчэйн технологи сэтгүүл зүйн хөгжлийг тодорхойлогч хүчин зүйл болох ньХураангуй: Блокчэйн технологи сэтгүүл зүйн хөгжилд цөөнгүй нөлөөг үзүүлж байна. Бид уг өгүүлэлдээ блокчэйн технологийн хэвлэл мэдээллийн салбарт үзүүлж буй нөлөө, боломж, нэвтрүүлэхэд тулгарах бэрхшээлүүд болон тус технологийн сэтгүүл зүйн хөгжилд хэрхэн хувьсал хийх боломжтойг тодорхойлж, блокчэйнд суурилсан хэвлэл мэдээллийн хэрэгслийн математик загварчлалыг боловсруулах үндсэн зорилгын хүрээнд бэлтгэв.Блокчэйн технологи нь сэтгүүл зүйн салбарт хуурамч мэдээлэлтэй тэмцэх, мэдээллийн гарал үүслийг баталгаажуулах, төвлөрсөн бус платформ бий болгох зэрэг олон давуу талтай. Мөн криптовалют ашиглан сэтгүүлч, редакцын санхүүгийн хараат бус байдлыг хангах, оюуны өмчийг хамгаалах, ил тод байдлыг нэмэгдүүлэх боломжтой. Гэсэн хэдий ч энэ технологийг бүрэн нэвтрүүлэхэд санхүү, хэрэглэгчдийн технологийн мэдлэг, хууль эрх зүйн зохицуулалт зэрэг хүндрэлүүд тулгарч байна.Түлхүүр үг: Баримтыг нягтлах, Хуурамч мэдээлэл, Төвлөрсөн бус платформ, Криптовалют, Ил тод байдал, Үйлчлүүлэгчийн бүрэн мэдээлэл